Methylphenidate and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The effects of methylphenidate in ten children with attention deficit complicated by seizure disorders are reported from the Departments of Pediatrics and Neurology, Children's Hospital of Pittsburgh, PA.